2000
DOI: 10.1016/s0035-9203(00)90274-8
|View full text |Cite
|
Sign up to set email alerts
|

Two-year impact of praziquantel treatment for Schistosoma japonicum infection in China: re-infection, subclinical disease and fibrosis marker measurements

Abstract: We studied a community cohort of 193 individuals exposed to endemic Schistosoma japonicum infection in the Dongting Lake region of China to assess subclinical morbidity and the 2-year benefit of curative therapy (praziquantel) administered in 1996. Prevalence and intensity of S. juponicum infection before treatment were 28% and 192 eggs per gram faeces (epg), respectively. Two years after cure, 22% of the cohort were reinfected, but with a lighter intensity (67 epg). Sixty-four subjects (37%) showed significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
33
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 32 publications
2
33
1
Order By: Relevance
“…In Tanzania, a correlation between serum C-IV and clinical and sonographic signs of hepatosplenic schistosomiasis was observed, but it did not have enough sensitivity to be useful as a screening tool for fibrosis (Kardorff et al 1999). Two independent groups in China found C-IV to be higher in subjects infected with Schistosoma japonicum (Guangjin et al 2002) and to correlate with re-infection after treatment of schistosomiasis japonica with praziquantel (Li et al 2000). Wyszomirska et al (2005Wyszomirska et al ( , 2006 investigated C-IV for the detection of schistosomiasis-related liver fibrosis in a tertiary care hospital in Brazil.…”
Section: Discussionmentioning
confidence: 99%
“…In Tanzania, a correlation between serum C-IV and clinical and sonographic signs of hepatosplenic schistosomiasis was observed, but it did not have enough sensitivity to be useful as a screening tool for fibrosis (Kardorff et al 1999). Two independent groups in China found C-IV to be higher in subjects infected with Schistosoma japonicum (Guangjin et al 2002) and to correlate with re-infection after treatment of schistosomiasis japonica with praziquantel (Li et al 2000). Wyszomirska et al (2005Wyszomirska et al ( , 2006 investigated C-IV for the detection of schistosomiasis-related liver fibrosis in a tertiary care hospital in Brazil.…”
Section: Discussionmentioning
confidence: 99%
“…Hepatic fibrosis, especially grade II and grade III, is a sound marker for chronic schistosomiasis japonica. 36,37 In this study, seropositive individuals with a history of recent contact with cercariae-infested water were examined by ultrasonography, and those with typical pathological features were defined as cases with chronic schistosomiasis. Cases concurrently diagnosed with other diseases (for example, hepatitis B and C) were excluded to avoid confounding when estimating the disability weight attributable to chronic schistosomiasis japonica.…”
mentioning
confidence: 99%
“…Thirdly, a 2-year cohort study of liver morbidity due to S. japonicum showed that after a single treatment with praziquantel, sub-clinical liver morbidity was significantly reduced (Li et al, 2000), but even after 5 years followup the resolution was not complete (Li et al, 2002). It was concluded that pathological changes around the portal tree might regress to a large degree but that 'network pattern' abnormalities do not normally resolve (Richter, 2000).…”
Section: Discussionmentioning
confidence: 99%